A Study on Students’ Attitudes towards Peer Review in Online Writing Classes - Emilia Ninik Aydawati; Anton Suratno (Universitas PGRI Semarang, 2023)
Abstract. Online peer review has been applied in Academic writing classes and it has had a positive impact on the students’ writing skills. Further study was done to find out the students’ attitudes toward online peer review in online writing classes. A questionnaire on students’ attitudes was distributed to 43 students in academic writing classes who are practicing online peer review. The statements in the questionnaire cover their attitude towards online peer review in three aspects: affective strategies, writing processes, and interaction ability. The findings show that the students have a positive attitude towards online peer review. They have a positive attitude toward the aspects. However, the students have a negative attitude one of the statements in social interaction ability. The average students do not see that this online peer review helps them learn about maintaining harmony in pair work.